Water Accounting Plus: limitations and opportunities for supporting integrated water resources management in the Middle East and North Africa - Amdar, Nafn; Mul, M.; Al-Bakri, J.; Uhlenbrook, S.; Rutten, M.; Jewitt, G. (Informa UK Limited, 2024)
This research explores the limitations and opportunities of Water Accounting Plus (WA+) for addressing water management issues in the MENA, focusing on Jordan. A comprehensive literature review and interview-based analysis were conducted to identify prevalent water management issues and evaluate information used in decision-making and strategy appraisals. The findings suggest that WA+ can enhance the spatio-temporal coverage of water resource assessments, refine estimates of irrigation water consumption, and facilitate demand management. Quantifying recharge and surface runoff requires integrating WA+ with hydrological models. Addressing climate change’s impact on future water resources requires integrating climate change projections with WA+.